Correlation between total prostate specific antigen and histological grading of prostate cancer in Kenyan mission hospital: a five-year retrospective review - Chinonso Paul Shu; Marius J. Tchinde; Tsamayem Georter James Sop; Signang Alberic Ndonku; Paul Irungu Juma (BMC Urology)
Abstract Background Prostate cancer (CaP) is the leading non-cutaneous cancer in men of African descent, with the higher mortality rates found in sub-Saharan Africa. Early diagnosis, staging, and management of prostate cancer could help curb its mortality rate in SSA. However, access to precise radiological imaging for staging purposes is limited in our setting. We sought to evaluate the correlation between total prostate specific antigen (tPSA) and histological grading of CaP in our resource-limited setting. Method We conducted a retrospective review of records of patients treated for biopsy-proven CaP at the AICKH diagnosed between January 2018 and December 2022. We excluded patients who were already on any sort of treatment of bladder outlet obstruction and incomplete charts. We used Spearman correlation coefficients, and ANOVA to evaluate the relationship between tPSA and various grading parameters. A P-value less than 0.05 was considered significant. Results We included 327 medical records. The mean tPSA was 112 ± 4.5ng/ml. The most common Gleason score and grade group were 8 (33.8%) and 4 (33.8%) respectively. Perineural involvement was present in 33% of our population. The tPSA had a positive correlation with Gleason score (rho = 0.253, p < 0.001), grade group (rho = 0.296, p < 0.001), perineural involvement (rho = 0.241, p = 0.001) and proportion of sample invasion (rho = 0.171, p = 0.005). A linear and homogenous variance existed in mean tPSA across increasing Gleason score (p < 0.001). Conclusion tPSA is a good predictor of the severity of CaP in resource-limited settings and can be used to inform management decisions.